The Agrarian Sector in Pakistan's Development Process - Historical Evidence and Implications for Policy and Theory (The Distinguishedl Lecture) (The Pakistan Development Review, 1989)
In 1947, Pakistan was a mere agricultural country. A few factories, especially for processing cotton and sugar could only be found in the cities of Karachi and Lyallpur. The young nation's main task in the initial years was to secure its population's survival, to integrate millions of refugees from India and to legitimize the new state. In an agricultural country, it was not surprising that the fIrst political approaches were made in agriculture. While the agrarian reform measures of the first years were not very drastic, the abolition of intermediaries was rather successful. This measure could be enforced because it did away with colonial relics. It was far more diffIcult to enforce a ceiling legislation, although land was urgently needed for distribution to refugees. For the development process, the structure of the country's elite was a deter- mining influence. It was, and still is, pluralistic with landowners, military men and higher administrative officers - and these often in close relationships - sharing power in the initial years. An industrial elite developed some years later only, consisting mainly of families migrating from India. The landowners were of decisive importance during that time. The large landowners practised mostly a policy which has been characterized as "rental feudalism". The land was rented to small tenants, and landlords cared little about improving agriculture but tried to earn higher incomes by strict control of the rent. Their aim was not to increase the production but increase the skimmed off part of the yield. Of course, there were also numerous small and medium farms, but their efficiency was liIpited. They practised traditional farming. Improved seed varieties, fertilizers, etc., were not available and the irrigation system had many shortcomings, especially as far as management is concerned. Salinity became more widespread. The objectives of these smaller farms were self-sufficiency and barter at the local level. Lacking infrastructure even made it difficult to produce for the market.